MU’JAM LUGHAWIY DAN PEROBLEMATIKA PENGGUNAANNYA DALAM PEMBELAJARAN BAHASA ARAB PADA MAHASISWA DI KOTA BIMA - Ahmad Syagif (Fitrah, 2022)
Mu'jam Lughawiy has crucial or even inseparable uses. Mu'jam Lughawiy has become a favorite tool for language learners. especially when faced with activities to find the meaning of a word. grammar. or the context of its use in the desired language. History also records that Mu'jam Lughawiy went through several stages of development. both in terms of its composition and the systematics of its writing along with its pluses and minuses. So therefore. This paper seeks to identify the problems faced by students in Bima City when using Mu'jam Lughawiy in learning Arabic. This paper can contribute positively to educators. learners. as well as foreign language practitioners, especially Arabic as initial information related to the problems faced by students when using Mu'jam Lughawiy so that they can be used as references in finding alternative solutions to various obstacles encountered when interacting with Mu'jam Lughawiy. This study applies a qualitative approach through the case study method and uses semi-structural interviews as a data collection technique and thematic analysis methods as a data analysis technique that has been obtained. In determining students as participants. The author applies a purposive sampling technique based on the student population at Islamic Higher Education in the City of Bima. This paper concludes that students' problems when using Mu'jam Lughawiy in Arabic learning are dominated by linguistic factors due to weak grammatical abilities as a result of weak learning motivation and problems in the Arabic learning process at the previous level. Students are more interested in interacting with Mu'jam Lughawiy in the form of software that uses an articulation system because of the financial efficiency factor.